Familial partial lipodystrophy resulting from loss-of-function PPARγ pathogenic variants: phenotypic, clinical, and genetic features - Soares, Reivla Marques Vasconcelos; da Silva, Monique Alvares; Campos, Julliane Tamara Araújo de Melo; Lima, Josivan Gomes (Frontiers in Endocrinology, 2024)
The PPARG gene encodes a member of a nuclear receptor superfamily known as peroxisome proliferator-activated gamma (PPARγ). PPARγ plays an essential role in adipogenesis, stimulating the differentiation of preadipocytes into adipocytes. Loss-of-function pathogenic variants in PPARG reduce the activity of the PPARγ receptor and can lead to severe metabolic consequences associated with familial partial lipodystrophy type 3 (FPLD3). This review focuses on recent scientific data related to FPLD3, including the role of PPARγ in adipose tissue metabolism and the phenotypic and clinical consequences of loss-of-function variants in the PPARG gene. The clinical features of 41 PPARG pathogenic variants associated with FPLD3 patients were reviewed, highlighting the genetic and clinical heterogeneity observed among 91 patients. Most of them were female, and the average age at the onset and diagnosis of lipoatrophy was 21 years and 33 years, respectively. Considering the metabolic profile, hypertriglyceridemia (91.9% of cases), diabetes (77%), hypertension (59.5%), polycystic ovary syndrome (58.2% of women), and metabolic-dysfunction-associated fatty liver disease (87,5%). We also discuss the current treatment for FPLD3. This review provides new data concerning the genetic and clinical heterogeneity in FPLD3 and highlights the importance of further understanding the genetics of this rare disease.